EP620 Characterisation of the microbiome along the female genital tract and rectum in endometrial cancer. (1st November 2019) - Semertzidou, A; MacIntyre, D; Marchesi, J; Bennett, P; Kyrgiou, M
Abstract : Introduction/Background: Endometrial cancer has a dominant place among gynaecological cancers and is the fourth most common malignancy in women after breast, lung and colorectal disease. Approximately, 2.9 percent of women will be diagnosed with uterine cancer at some point during their lifetime. The intricate relationship between microbes and oncogenesis remains largely obscure. Microorganisms are implicated in 20% of human malignancies and there is currently a wealth of evidence to support this.Functional links between the female genital tract (FGT) microbiome and endometrial cancer have not been established yet, which makes this project conceptually pioneering. Methodology: Patients with endometrial cancer and benign controls were recruited within Imperial College Healthcare NHS Trust. Eligibility criteria included patients undergoing total hysterectomy with or without bilateral salpingo-oophorectomy either laparoscopically or transabdominally. Microbiome swabs were collected along the female genital tract (lower 2/3 and higher 1/3 of vagina, external cervical os, lower endometrium, fundal endometrium, fallopian tubes and ovaries) and rectum. Bacterial DNA was extracted using QiAmp Mini DNA kit (Qiagen, Venlo, Netherlands). The V1-V2 hypervariable regions of 16S rRNA genes were amplified by PCR and microbial profiling was conducted using a MiSeq platform (Illumina, San Diego, CA, USA). The 16S rRNA gene sequence data were analysed with Mothur software package and OTU taxonomies (from Phylum to Species) were determined. Results: 65 patients were recruited subdivided into 42 patients with endometrial cancer and 23 with benign conditions.Most common benign indications for hysterectomy were fibroids and dysfunctional uterine bleeding.We observed that bacterial composition and richness differ between women with endometrial cancer and benign controls. In particular, women with endometrial cancer display lower bacterial diversity and richness along their genital tract. Additional evidence will be presented at the conference. Conclusion: The microbial landscape of women with endometrial cancer differs from that of benign controls. Disclosure: Nothing to disclose.